Proceedings of the 2018 International Conference on Advanced Visual Interfaces 2018
DOI: 10.1145/3206505.3206524
|View full text |Cite
|
Sign up to set email alerts
|

Impact of semantic aids on command memorization for on-body interaction and directional gestures

Abstract: Figure 1: (a) Using BodyLoci, the user selects a command by touching an area on his body; (b) using mid-air Marking menus, the user selects a command by performing a directional gesture in front of him; (c) hardware setup in the virtual reality context; (d) novice modes with background images for both techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 47 publications
1
8
0
10
Order By: Relevance
“…We observed that 66.6% of the subjects formed groups of commands to facilitate memorization. This type of strategy has also been observed in other studies [7,13,24]. It is interesting to note that the majority of participants used this method without being instructed to do so.…”
Section: Research Leads and Suggestionssupporting
confidence: 76%
See 4 more Smart Citations
“…We observed that 66.6% of the subjects formed groups of commands to facilitate memorization. This type of strategy has also been observed in other studies [7,13,24]. It is interesting to note that the majority of participants used this method without being instructed to do so.…”
Section: Research Leads and Suggestionssupporting
confidence: 76%
“…Once the user has learned a set of gestures, he can perform them quickly without being guided. Several studies showed that such gestures could be efficiently memorized (e.g., [3,13,26]) and that they provide advantages over keyboard shortcuts [1]. User customization can also improve memorization [22], as well as the degree of effort needed for performing gestures [10].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations